Clinicopathological Features of Thyroid-Like Low-Grade Nasopharyngeal Papillary Adenocarcinoma: A Case Report and Review of the Literature - Takakura, Hiromasa; Hamashima, Takeru; Tachino, Hirohiko; Nakazato, Akira; Minato, Hiroshi; Sasahara, Masakiyo; Shojaku, Hideo (Frontiers in Surgery, 2020)
Thyroid-like low-grade nasopharyngeal papillary adenocarcinoma (TL-LGNPPA) is an extremely rare neoplasm of the nasopharynx. Accordingly, its clinical and pathological characteristics are not well known. We report a case of TL-LGNPPA and review the relevant literature on TL-LGNPPA. A 38-year-old Japanese woman presented with a history of nasal obstruction that had persisted for one month after symptoms of a common cold (e.g., low-grade fever, sore throat, and fatigue). A pedunculated tumor of approximately 20 mm in diameter was found on the posterior edge of the nasal septum. The tumor was endoscopically resected. Based on careful histopathological and immunohistochemical examinations, it was diagnosed as TL-LGNPPA. At 5 years after surgery, the patient remained disease-free. TL-LGNPPA has a very good prognosis, and complete resection with a sufficient safety margin is recommended as the first-line treatment. The morphological characteristics and immunohistochemical findings, especially TTF-1 positivity and thyroglobulin negativity, are important for the diagnosis.